Data Analysis of E-Journal Usage in UPM Library with K-Means Clustering Method - Sugiyarto, Susi Rachmadhani; Rahmi, Rahmi (Information Technology and Science (ITScience), 2025)
This study aims to evaluate the usage patterns of Emerald and WileyOnline Library e-journals from January to December 2023. By employing the K-Means clustering method, the data were classified to analyze usage characteristics and efficiency. The clustering results indicate that journals in clusters C1 and C2 have higher relevance compared to those in C3, based on download and access numbers. Evaluation using three metrics—average cost per e-journal, average cost per access, and appropriate content usage—revealed that e-journal usage at the UPM library is not yet efficient, with high average costs per access and content usage needing improvement. This study recommends strategies to enhance the efficiency of e-journal usage to better support academic activities and research at UPM.